2020
DOI: 10.1039/d0sm00320d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polar amino acid incorporation on Fmoc-diphenylalanine-based tetrapeptides

Abstract: The incorporation of polar amino acids into the Fmoc-FF motif yields tetrapeptide hydrogels whose biocompatibility in the gel state is inversely proportional to their biocompatibility in the solution state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Fmoc-tetrapeptides Fmoc-XXFF where X indicates a polar residue, i.e., charged D, E, R or K or neutral N or Q have been prepared and studied . Fibrils were observed for all conjugates containing charged residues but not those with neutral N or F. Hydrogels were observed for all conjugates via pH switch using GdL.…”
Section: Fluorenylmethyloxycarbonylmentioning
confidence: 99%
See 2 more Smart Citations
“…Fmoc-tetrapeptides Fmoc-XXFF where X indicates a polar residue, i.e., charged D, E, R or K or neutral N or Q have been prepared and studied . Fibrils were observed for all conjugates containing charged residues but not those with neutral N or F. Hydrogels were observed for all conjugates via pH switch using GdL.…”
Section: Fluorenylmethyloxycarbonylmentioning
confidence: 99%
“…Fibrils were observed for all conjugates containing charged residues but not those with neutral N or F. Hydrogels were observed for all conjugates via pH switch using GdL. The cytotoxicity was also examined along with interactions with tethered lipid membranes . Fmoc-tetrapeptides DAAR or DGGR contain dialanine or diglycine substrates for enzymes including chymotrypsin, elastase or thermolysin.…”
Section: Fluorenylmethyloxycarbonylmentioning
confidence: 99%
See 1 more Smart Citation
“…Short peptides and their analogues have been attracting great interest in recent years as building blocks for soft matter. [1][2][3][4][5][6][7] They offer several advantages over other molecular classes, such as ease of preparation and scale-up, low cost, inherent biocompatibility and biodegradability, as well as the possibility to encode biological messages. 8 In particular, it has been shown that a sequence as short as a tripeptide possesses, on average, the ideal number of non-carbon atoms required to maximise ligand-receptor interactions to develop drug-like molecules.…”
Section: Introductionmentioning
confidence: 99%